Determinants of motor vehicle taxpayer compliance in the Province of Yogyakarta Special Region - Ahyar, Ahyar; Filiana, Filiana; Mulyati, Asrah (Priviet Social Sciences Journal, 2026)
Motor vehicle tax is one of the main sources of revenue for local governments in Indonesia, including the Special Region of Yogyakarta (DIY) province. This study aims to examine the influence of variables, such as attitude, subjective norm, behavioral control, taxpayer awareness, religiosity, service, and tax sanctions, on motor vehicle taxpayers’ compliance in the DIY province. The study employs a quantitative approach and utilizes partial least squares (PLS) analysis with the assistance of the SmartPLS 3 application. The sample size for this study comprised 150 motor vehicle taxpayers in the DIY province. The research findings indicate that attitude, behavioral control, taxpayer awareness, service, and sanctions variables have an impact on taxpayer compliance. Meanwhile, subjective norm and religiosity variables do not influence compliance with motor vehicle taxpayers in the DIY province.